A high-precision silicon-on-insulator position sensor - Beck, Paul; Wynne, Laura C.; Iadanza, Simone; O’Faolain, Liam; Schulz, Sebastian A.; Banzer, Peter (APL Photonics, 2023)
Integrated photonic devices provide significant advantages over their conventional counterparts, such as a drastically reduced footprint as well as compatibility with other photonic or electronic circuitry. In this work, we present a high-precision optical position sensor fabricated on a silicon-on-insulator platform. The sensor relies on the principle of position-dependent directional waveguide coupling upon excitation of a monolithically integrated scatterer with a tightly focused polarization-tailored beam. We demonstrate a spatial resolution of 7.2 nm, corresponding to approximately λ/200.
CRIS-Team Scopus Importer:2023-05-19